Стихи и песни - Тальков Игорь Владимирович (Самое лучшее, самое любимое, 2003)
Экземпляры: ф.11 (20210416) / Инвентарный номер: 60835 / Цена: / Сис.шифр: 84(2=411.2)6-5 / Авт.знак: Т 16 / ГРНТИ: 17.82.10 / ББК: 84(2=411.2)6-5